The association of smokeless tobacco use and pack-years of smokeless tobacco with age-related macular degeneration in Indian population. (3rd July 2017) - Srinivasan, Sangeetha; Swaminathan, Gayathri; Kulothungan, Vaitheeswaran; Sharma, Tarun; Raman, Rajiv
Abstract: Aim : To explore the association of use versus no use and the influence of pack-year use of smokeless tobacco with that of early and late age-related macular degeneration (AMD) in rural and urban south Indian population. We hypothesized that the use and pack-years of use would be significantly associated with both early and late AMD. We therefore sought to examine subjects who gave a history of using smokeless tobacco and we quantified the usage as pack-years, to examine the association with that of early and late AMD. Materials and methods : This was part of Sankara Nethralaya: Rural–Urban Age-related Macular degeneration study (SN-RAM study), which was conducted between 2007 and 2010. Subjects aged 60 years or older or those turning 60 in the present calendar year, with a history of using smokeless tobacco were noted along with duration and number of packs used per day. Smokeless tobacco was defined as chewed-tobacco (loose leaves) and/or snuff (finely chopped tobacco). Subjects underwent detailed ophthalmic evaluation including cataract grading using the Lens Opacities Classification System (LOCS III), 45° 4-field stereoscopic fundus photography and AMD evaluation. Pack-years of smokeless tobacco use was stratified as <15, 15–34 and ≥35 years; the association of tobacco use and pack-years of use with that of early and late AMD was examined. A p value of < 0.05 was considered statistically significant. Results : The number of smokeless tobacco users was significantly higher in rural ( n = 767) than in urban groups ( n = 281), p < 0.001. Of the 1048 users, 238 subjects (23%) provided details regarding quantification of use. There were no significant differences in the pack-years between rural and urban areas, p = 0.756 or that between AMD and no AMD, p = 0.562. Use of smokeless tobacco compared with no use was significantly associated with late AMD, OR= 3.178, 95%CI: 1.095, 9.227, p = 0.033, when adjusted for age, gender, rural-urban differences, presence of diabetes, socioeconomic status, systolic and diastolic blood pressure, total cholesterol, low-density and high-density lipoprotein levels. The association was not significant for early AMD, p = 0.582. The pack-years of use did not show a statistically significant association with early or late AMD. Furthermore, out of the 1048 subjects, 547 reported as using areca nut. Of which, 415 (75.8%) subjects had no AMD, 119 (21.7%) showed evidence of early AMD and 13 (2.4%) had late AMD. There was no significant association between the use of areca nut and early AMD, ( X 2 (1, N = 930) = 2.345, p = 0.126) or with that of late AMD ( X 2 (1, N = 761) = 0.075, p = 0.785). Conclusions : Smokeless tobacco use compared with no use, is associated with late AMD, regardless of the pack-years of use. Tobacco use is a modifiable risk factor. Efforts to reduce or stop the use of smokeless tobacco is indicated in an effort to prevent vision loss with respect to late AMD.